2023
DOI: 10.3390/polym15153201
|View full text |Cite
|
Sign up to set email alerts
|

Particle Shedding from Cotton and Cotton-Polyester Fabrics in the Dry State and in Washes

Abstract: The influence of 3, 10 and 50 washing cycles on the properties of cotton fabric and cotton-polyester blend in plain weave, was investigated in this study. In addition to the analysis of tensile properties in weft and warp directions and thickness, the number of particles produced in the dry state was also measured after 3, 10 and 50 washes. After washing, the entire effluent was analysed by determining the total suspended solids (TSS), the total solids (TS), the pH value and the conductivity. To determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…The standard deviation for all elongations at break for unaged and aged materials is low, and there are no statistically significant differences between elongations at break. These results are in contrast to the study by Pušić et al, who show that aging has a significant influence on the change in elasticity of the polyester material [ 31 ].…”
Section: Resultscontrasting
confidence: 99%
“…The standard deviation for all elongations at break for unaged and aged materials is low, and there are no statistically significant differences between elongations at break. These results are in contrast to the study by Pušić et al, who show that aging has a significant influence on the change in elasticity of the polyester material [ 31 ].…”
Section: Resultscontrasting
confidence: 99%
“…For each sample, the measurements were performed on 5 test tubes. This method was adopted from EN ISO 9073-10 [37] Textiles-Test methods for nonwovens-Part 10: Lint and other particles generation in the dry state, with the test time adjusted to 30 min [19,20]. Due to the large number of particles released in total, the number of particles is displayed graphically in logarithmic values for easier presentation of the results.…”
Section: Test On Laser Particle Counter Lasair III (Particle Measurem...mentioning
confidence: 99%
“…The amount of textile dust produced can be reduced by choosing a suitable raw material composition and by optimising the structural and morphological characteristics of the fabrics such as yarn fineness and crimp, fabric density and weave of the fabric. The surface of the fabric wears out with use and care, resulting in the release of textile dust [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the degradation of the polymer occurs in the crystalline phase. As for polymers for apparel applications, the aging protocol should consider the regular care process as well as the polymer treatments, in addition to the environmental factors in aging [ 23 , 24 , 25 , 26 ]. As reported in studies, the care factors themselves can influence the increase of material strength as a result of polymer fibrillation and material shrinkage [ 27 ].…”
Section: Introductionmentioning
confidence: 99%